ANALISIS NILAI TAMBAH IKAN TUNA MENJADI ABON IKAN TUNA PADA INDUSTRI RUMAH TANGGA “RAJA BAWANG” DI KELURAHAN BIROBULI KECAMATAN PALU SELATAN DI KOTA PALU - Haspian, Haspian; Howara, Dafina (AGROTEKBIS, 2018)
The fisheries as one of the support sub-sector of the agricultural sector in the economy has a role in national economic development. These roles provide added value and strategic value, as well as provide financial and economic benefits, particularly in the provision of protein foodstuffs, foreign exchange earnings, and the provision of jobs. This study aims to determine the added value obtained by tuna fish after being processed into tuna shreds in the home industry of Raja Bawang in Palu City. This research was conducted on Raja Bawang home industry in Palu City, the location determination was done purposively, considering that Raja Bawang home industry is an industry that has been producing tuna fish shreds. The study was conducted from March to April 2017. Respondents in this study were the leaders and employees of Raja Bawang household industry in Palu City. The analysis used is value-added analysis (Hayami Method). Based on the results and discussion of the research, it can be concluded that the production of tuna fish on the Raja Bawang home industry during April of 2017 using 75 kg of tuna fish and produce as many as 500 packs of abon tuna the amount of production of abon tuna fish in Raja BawangIndustry is Rp.4,558,838 and the added value obtained from processed tuna fish into tuna shred as much as Rp.62.995 / kg, with profit of Rp.29.934 or as much as 47,51%.